Effect of Oblique SV Wave on the Seismic Response of Mountain Tunnel - Mingxing Cao; Songhong Yan; Jiaxuan Du; Weiyu Sun; Yuxiang Li; Junjie Zhao (Advances in Civil Engineering)
In order to study the dynamic response of parallel mountain tunnels under the oblique incidence of seismic waves, based on the display finite element method and using viscoelastic artificial boundary, the oblique incidence of three-way seismic waves was realized by angular incident mode. The displacement and stress distribution characteristics of the tunnel lining under different propagation angles and vibration angles of SV waves were studied. The results show that the oblique incidence of SV wave has a certain effect on the displacement of the double tunnel, the forces in the tunnel are symmetrical and the axis displacement increases with the increase of incident angle, and the vertical displacement changes greatly. The stress of the tunnel lining under the oblique incidence of the SV wave is elliptical. The peak value of the maximum principal stress appears at the maximum span on both sides, and the maximum principal stress decreases with the increase of the vibration angle. The maximum principal stress of the right tunnel is flat. The minimum principal stress of the left and right holes decreases with the increase of vibration angle, and the minimum principal stress of the left hole is 90°∼270°. The distribution of the minimum principal stress in the range is large. Mises stress increases with the increase of the incidence angle of seismic waves.